PENDEKATAN SWOT DALAM PENGEMBANGAN OBYEK WISATA SITU GEDE DI KOTA TASIKMALAYA - R. Soni Somali; Tuti Iriani; Mila Karmila; M. Abdul Aziz Danu Brata; Indah Sugiarti (Jurnal Cakrawala Ilmiah, 2023)
The development of tourism in an area will certainly have a positive impact on society both economically and socially and culturally. The city of Tasikmalaya has many tourist attractions that can be visited and become icons. One of them is the Situ Gede tourist attraction. Situ Gede tourism object is one of the recommended tourist destinations in Tasikmalaya because it has quite an interesting charm to visit. However, not enough people know about this interesting tourist attraction. Therefore a strategy is needed to influence people's interest in visiting this tourist attraction. This research uses the concept or method of qualitative research (descriptive qualitative) SWOT approach, namely by examining alternative strategies for planning and developing the Situ Gede Tasikmalaya tourist attraction based on internal and external environmental analysis. The respondents of this study were visitors to the Situ Gede Tasikmalaya tourist attraction. The result of the SWOT application is an analysis of the internal and external environment that influences people's interest in visiting the Situ Gede tourist attraction.